PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMK NEGERI 7 MBD - Hiwy, Jafet; Molle, Selvesina J; Laamena, Christina M (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2021)
This research aims to find out the improvement of student learning outcomes in the material of rank numbers, root forms and logarithms by applying the discovery learningmodel, The subjects in this study are students of class X majoring in NKPI SMK Negeri 7 MBD which amounted to 18 students. This study is a classroom action study with the teacher acting as a teacher and lasts for 2 cycles. Data collection is done using tests and observation results, Data analysis techniques use quantitative analysis and qualitative analysis. The results of the analysis showed that there was an increase in student learning outcomes from cycle I obtained 27.78% (5 students) who reached KKM. to cycle II obtained 72.22% (13 students) who reached KKM From the results obtained, the discovery learning type cooperative learning model can improve students' learning outcomes in graded biloangan material, root form and logarithms.